Post Pandemic Indonesian Regional Development Planning, New Normal, New Orientation: The Case of West Java - Satya Laksana (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2021)
Corona Virus Diseases (Covid-19) outbreak has impacted almost all aspects of life including regional development planning in Indonesia. The new regional development planning orientation per se adjusts the new habits of citizens in the new normal era which is well-known as the Internet of Things (IoT) lifestyle. This paper elaborates on the post-pandemic development orientation of the West Java Province by answering three problem statements: 1) What is the Government Policy in dealing with the Covid-19 pandemic; 2) What is the condition of existing IoT Infrastructure in Regencies and municipalities in West Java Province, and 3) what is the new development orientation of West Java Province based on the existing conditions. By utilizing dataset from the Government’s official website and elaborating relevant articles in scientific journals and news in mass media, it discusses intended issues thematically with a deductive approach. The discussion covers the author’s outlook of the new development orientation on three sectors: 1) education, 2) infrastructure and 3) bureaucratic reform. Policy implications are discussed.